âGENDHISâ BALUTAN GONI DAN BLACU SEBAGAI ASIMILASI AKSESORIS ETNIK DAN MODERN - Widya Ninggar, Gisca Ajeng; Christyandari, Sisilia; Pradita, Melinda; Wuryani, Indah Putri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Nowadays, accessories are transformed to required object for women, as their attention was no longer just for clothing, but also point to what and how accessories used to beautify their appearance. Thus, ethnic-modern accessories are going to be an alternative for women to looked beautiful in a simply way. Various materials have been used for this stuff, but weâre barely finding the use of jute and calico. Whereas, jute and calico are easy to find and their priceâs quite affordable. Using calico and jute as base materials for contemporary accessories will increase their art value, yet still on reasonable price and good quality. The method used here are subdivision of the organizational structure, production, promotion through offline and online media, and distribution. The result of this program is for creating new handicraftâs innovation. Besides, this also purposed to create new jobs for our partner.Â Keywords: Innovation, Accessories, Contemporary, Calico, Hessian